Efficacy of combined tumor irradiation and KCa3.1-targeting with TRAM-34 in a syngeneic glioma mouse model - Nicolai Stransky; Katrin Ganser; Leticia Quintanilla-Martinez; Irene Gonzalez-Menendez; Ulrike Naumann; Franziska Eckert; Pierre Koch; Stephan M. Huber; Peter Ruth (Scientific Reports, 2023)
Abstract The intermediate-conductance calcium-activated potassium channel KCa3.1 has been proposed to be a new potential target for glioblastoma treatment. This study analyzed the effect of combined irradiation and KCa3.1-targeting with TRAM-34 in the syngeneic, immune-competent orthotopic SMA-560/VM/Dk glioma mouse model. Whereas neither irradiation nor TRAM-34 treatment alone meaningfully prolonged the survival of the animals, the combination significantly prolonged the survival of the mice. We found an irradiation-induced hyperinvasion of glioma cells into the brain, which was inhibited by concomitant TRAM-34 treatment. Interestingly, TRAM-34 did neither radiosensitize nor impair SMA-560’s intrinsic migratory capacities in vitro. Exploratory findings hint at increased TGF-β1 signaling after irradiation. On top, we found a marginal upregulation of MMP9 mRNA, which was inhibited by TRAM-34. Last, infiltration of CD3+, CD8+ or FoxP3+ T cells was not impacted by either irradiation or KCa3.1 targeting and we found no evidence of adverse events of the combined treatment. We conclude that concomitant irradiation and TRAM-34 treatment is efficacious in this preclinical glioma model.